Indonesian green tides: the problem is also the solution - Maggs, Christine A.; Harries, David; Priatna, Dolly (Indonesian Journal of Applied Environmental Studies, 2024)
Green tides are unattached blooms of green macroalgae (seaweeds) that occur globally and can attain vast proportions. The main components of the blooms are species of the sea lettuce genus Ulva, a sheet-like green seaweed, which can form unusual morphs under these conditions. In estuaries and shallow coastal embayments drifting or cast-up macroalgae can reach quantities of up to 27 kg wet weight m-2. Green tides have been researched extensively since Fletcher's (1996) review highlighted their importance, but they came to wide public attention at the time of the 2008 Qingdao Summer Olympics when the Yellow Sea blooms endangered the sailing events. In May–July 2008, prior to the Olympics, the Yellow Sea coastline experienced the world’s largest green tide with 1 million tonnes of drifting biomass covering 13,000–30,000 km2. Enormous quantities were washed into shallow water and onto the beaches.  News reports from the time show volunteers working to remove the biomass and save the events.  Green tides have increased in frequency and extent globally over the last few decades, with the most significant blooms continuing to be those in the Yellow Sea.